The Impact of Cardiac Output Methods on the Classification of Pulmonary Hypertension - Léon Genecand; Gaëtan Simian; Mona Lichtblau; Jean‐Marc Fellrath; Julian Klug; Hugues Turbé; Christian Lovis; Stéphane Noble; Julie Wacker; Julian Müller; Roberto Desponds; Maurice Beghetti; et al. (Pulmonary Circulation, 2025)
ABSTRACT Cardiac output is essential to calculate pulmonary vascular resistance (PVR) and classify pulmonary hypertension (PH). Recent evidence has shown a lower agreement between thermodilution (COTD) and direct Fick (CODF) methods than historically estimated. The influence of the cardiac output measurement method on the classification of PH is poorly explored. We aimed to estimate the risk of diagnostic error when using COTD instead of CODF. We used a previously published mathematical model to consecutive patients diagnosed with PH at three centers in Switzerland. This model allows an individual estimation of the risk of diagnostic error when using COTD instead of CODF and is based on limits of agreement (LoA) between COTD and CODF of 2 L/min (average estimation) and 2.7 L/min (worst case scenario estimation). One thousand one hundred and forty‐two patients with PH were evaluated. The mean risk of diagnostic error using the model with LoA of 2 L/min was 6.0% in the overall population (n = 1142). The mean risk of diagnostic error was 2.9% among the 712 patients with precapillary PH, 15.0% among the 113 patients with isolated postcapillary PH (IpcPH), 7.2% among the 247 patients with combined post‐ and pre‐capillary PH, and 18.8% among the 70 patients with unclassified PH. The estimated diagnostic error when using COTD instead of CODF was generally low, particularly for patients with precapillary PH. Patients with PVR close to the diagnostic threshold of 2 WU (i.e., between 1 and 3 WU), mostly concerning patients with IpcPH and unclassified PH, exhibited a higher risk of diagnostic error.